2015
DOI: 10.5152/balkanmedj.2014.13265
|View full text |Cite
|
Sign up to set email alerts
|

Fracture History in Osteoporosis: Risk Factors and its Effect on Quality of Life

Abstract: Forearm, ankle and foot fractures can be commonly seen in osteoporosis patients with fracture history. We suggest that it is important to recognise osteoporosis prior to first fracture and disease-specific quality of life assessment should be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…The multiple linear regression results indicated that sex, age, race, previous fracture, BMI, smoking, and physical activity are significant for T2DM patients 6 , 8 , 27 , 29 35 , 44 – 48 . Thus these related risk factors might partially contribute to the declining trend in mean BMD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The multiple linear regression results indicated that sex, age, race, previous fracture, BMI, smoking, and physical activity are significant for T2DM patients 6 , 8 , 27 , 29 35 , 44 – 48 . Thus these related risk factors might partially contribute to the declining trend in mean BMD.…”
Section: Discussionmentioning
confidence: 95%
“…For the race/ethnicity groups, “Mexican American” and “Other Hispanic” were merged into a single group called “Hispanic,” and the remaining groups were “non-Hispanic White,” “non-Hispanic Black,” and “non-Hispanic other,” respectively. BMD-related variables, including body mass index (BMI), previous fracture 29 , 30 , smoking status 31 , 32 , physical activity 33 , 34 , and family history of osteoporosis 35 , were considered for analysis. BMI was derived from measured weight in kilograms, divided by the square of height in meters.…”
Section: Methodsmentioning
confidence: 99%
“…Incidence of cardiovascular and cerebrovascular diseases such as hypertension, coronary heart disease and cerebral infarction in the elderly osteoporosis group is higher than that of the elderly population with normal bone density. In addition, studies have shown that the use of low bone density as a risk factor for cardiovascular and cerebrovascular events and death may predict the occurrence of cardiovascular and cerebrovascular diseases and the progress of the disease and is more accurate than traditional risk factors such as smoking and hyperlipidemia (11). Logistic regression analysis in this study showed that hypertension, coronary heart disease, and cerebral infarction were the main risk factors for osteoporosis in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The trial population comprised of male or female patients of at least 50 years of age. In total, 50 patients with fractures of the vertebral body (TH7-L4) due to osteoporosis [14] or a trauma scheduled for one-staged kyphoplasty were consecutively screened and enrolled, and 49 were included in the safety population (SAF population). Exclusion criteria were known hypersensibility against ingredients of the tested bone cement, concomitant systemic gentamicin treatment, any concomitant disease (excluding a minimally invasive kyphoplasty of the vertebral body), presence of spondylitis or infection, renal impairment, sensorineural hearing loss, and hemorrhagic diathesis.…”
Section: Methodsmentioning
confidence: 99%